Anti- nucleosome antibodies- a valuable test in systemic iupus erythematosus - Abid, Ahmed A.; AL derzi, Aida R.; Albidri, Khudhayer Z. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Nucleosomes are fundamental units of chromatin released by internucleosomal cleavage during cell apoptosis, and nucleosomal material has been demostraded in the surface blebs of opoptotic cells. recent studies have shown the presence of antinucleosome antibodies in systemicc lupus erythematosus (SLE).